Influences of sex, sex composition of brood and hatching order on mass growth in common terns Sterna hirundo - Becker, Peter H.; Wink, Michael (Behavioral ecology and sociobiology, 2003)
We studied sex-dependent mass growth of chicks of the monomorphic common tern Sterna hirundo which fledged at a colony site in Wilhelmshaven, Germany, between 1997 and 1999. Brood size, brood mates' sex and hatching order (a-, b- and c-chicks) were known for many individuals, which were sexed by molecular techniques. Daily growth rates and age of fledging were independent of sex. However, in all years male chicks reached higher peak mass and fledged up to 5.2% heavier than female chicks. Broods with at least two fledglings showed that besides sex, brood size interacting with sex composition affected chick mass. In mixed broods, brothers had higher peak and pre-fledging mass than sisters they were reared with. Especially in the combination a-daughter and b-son the brothers were heavier. Lowest mass was found in broods with three nest mates of the same sex. A detailed study of 24 three-fledgling broods showed that male c-chicks were heavier than their siblings. The results reveal an advantage for chicks in mixed broods, especially for sons, and more especially if the son was a c-chick. Higher mass and possibly dominance of sons in c-position might be related to higher maternal androgen levels, which are known to increase with each egg laid. The results suggest that even in a monomorphic species, sons might be more expensive to rear, and are discussed with respect to sibling competition, parental effort, survival of sons, as well as to fitness benefits favoring parents producing sons.
Gesehen am 04.10.2017
DOI ist fehlerhaft